FACTORS AFFECTING STOCK PRICES IN INSURANCE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Arumsari, Rizki; Dewi, Riana R; Siddi, Purnama (STIE Kusuma Negara, 2020)
In this study aims to analyze the effect of profitability, leverage and company size on stock prices. Sources of data obtained from the financial statements of insurance companies listed on the Stock Exchange in 2014-2018. This type of research is quantitative. The population and sample used 9 purposive sampling techniques. The analytical method used is multiple linear regression, F test and T test The results of the study show that the profitability, leverage and company size variables simultaneously influence the stock price. While the partial analysis shows that the profitability variable has no effect and does not affect the stock price, the leverage variable also shows that there is a negative and significant influence on the stock price, the firm size variable has a positive and significant effect on the stock price. With the Determanation coefficient (Adjusted R2) contributing to the influence of profitability, financial leverage, and company size by 26.6%. while 73.4% is influenced by other variables. The benefit of this study is to provide additional information to researchers who will develop knowledge in the field of financial accounting.